Factors Influencing Liana Species Richness and Structure following Anthropogenic Disturbance in a Tropical Forest, Ghana. (9th December 2012) - Addo-Fordjour, Patrick; El Duah, Philip; Agbesi, David Kafui Kudjo
Abstract : The study was conducted to determine the factors that influenced liana species richness and structure in forests of different disturbance intensities (high, moderate, and low disturbance forests) in the Southern Scarp Forest Reserve, Ghana. Within each forest, lianas (dbh≥ 2 cm) were enumerated in six25 × 20 m 2 plots located along transects. Soil physicochemical properties and forest structure were determined within the plots. Liana species richness and abundance were significantly lower in the high disturbance forest (P < 0.001 ) whereas basal area was significantly higher in the low disturbance forest (P = 0.014 ). Tree abundance and dbh significantly predicted liana species richness and structure in the study (P < 0.05 ). On the basis of the importance value index, three main liana communities, each corresponding with a forest type, were identified. Stepwise multiple regression analysis revealed that exchangeable magnesium and calcium, and total exchangeable bases were the main soil variables that affected liana species richness. Liana structure was influenced by the above-mentioned soil variables as well as exchangeable potassium and sodium, and pH. The present study has demonstrated that changes in liana species richness and structure following human disturbance may be due to variations in soil properties and forest structure.